Koreksi Gummy Smile dengan Alat Ortodonti Cekat Kombinasi Miniscrew (Literature Review) - Ika Sukma Wulandari (Universitas Muhammadiyah Semarang, 2021)
Background: Gummy smile is a condition where the maxillary front gingiva looks excessive when someone smiles. This condition is often aesthetically unpleasant. There are several causes of gummy smile, the most common is alveolo-skeletal etiology. Treatment of gummy smiles with an alveolo-skeletal etiology is often performed by intrusion of anterior segment teeth. Recently, there have been several technique of tooth intrusions using fixed orthodontic appliances combined with miniscrews. Objective: To study the treatment results of gummy smile correction using orthodontic appliance combined with miniscrew. Conclusion: Treatment of gummy smile using orthodontic appliance combined with miniscrew gives satisfaying results in cases with alveolo-skeletal etiology, especially in patients with long faces.